An evaluation of the collection and reference services of selected health libraries in Quezon City - Perez, Marie Grace B. (2006)
Since medical and health libraries function as vital centers for continuing education of healthcare professionals, a closer analysis of its resources and services have to be developed to make the necessary changes in time to meet the demands of its library clientele. It is in light that this study focused on the collection and reference services available in the four selected health libraries in Quezon City (New Era University, World Citi Hospital and Colleges, Trinity College of Quezon City and Delos Santos Medical Center-STI). Aside from the head librarians, a total of 340 student clientele were surveyed (85 students in each institution). The Medical and Health Librarians Association of the Philippines' Guidelines and Standards for Collection Development in Medical and Health libraries served as the library collection evaluation tool for the four health libraries. Reference services cited in the works of the Medical Library Association, Katz and Tarr, and the Canadian Council of Federal Libraries were the basis of the reference services included in the survey questionnaire.